Electrocatalytic Actvity of Modified Gold Electrodes Based on Self-Assembled Monolayers of 4-Mercaptopyridine and 4-Aminothiophenol on Au(111) Surfaces Chemically Functionalized with Substituted and Unsubstituted Iron Phthalocyanines - Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Silva-Rojas, J; Silva-Rojas, J; Silva-Molina, C; Silva-Molina, C (2013)
Sin Editorial Disponible